Value of insoluble PABPN1 accumulation in the diagnosis of oculopharyngeal muscular dystrophy. (15th December 2019) - Galimberti, V.; Tironi, R.; Lerario, A.; Scali, M.; Del Bo, R.; Rodolico, C.; Brizzi, T.; Gibertini, S.; Maggi, L.; Mora, M.; Toscano, A.; Comi, G. P.; et al.
Abstract : Background and purpose: The aim was to assess the value of insoluble PABPN1 muscle fibre nuclei accumulation in the diagnosis of atypical cases of oculopharyngeal muscular dystrophy (OPMD). Methods: Muscle biopsies from a selected cohort of 423 adult patients from several Italian neuromuscular centres were analysed by immunofluorescence: 30 muscle biopsies of genetically proven OPMD, 30 biopsies from patients not affected by neuromuscular disorders, 220 from genetically undiagnosed patients presenting ptosis or swallowing disturbances, progressive lower proximal weakness and/or isolated rimmed vacuoles at muscle biopsy and 143 muscle biopsies of patients affected by other neuromuscular diseases. Results: The detection of insoluble nuclear PABPN1 accumulation is rapid, sensitive (100%) and specific (96%). The revision of our cohort allowed us to discover 23 new OPMD cases out of 220 patients affected with nonspecific muscle diseases. Conclusions: Oculopharyngeal muscular dystrophy is often misdiagnosed leading to diagnosis delay, causing waste of time and resources. A great number of these cases present symptoms and histological findings frequently overlapping with other muscle diseases, i.e. inclusion body myositis and progressive external ophthalmoplegia. PABPN1 nuclear accumulation is a reliable method for diagnostic purposes and it is safe and useful in helping pathologists and clinicians to direct genetic analysis in the case of suspected OPMD, even when clinical and histological clues are deceptive.